2014
DOI: 10.3390/soc4030463
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks as a Coping Strategy for Food Insecurity and Hunger for Young Aboriginal and Canadian Children

Abstract: Traditional foods and food sharing are important components of Aboriginal culture, helping to create, maintain, and reinforce social bonds. However, limitations in food access and availability may have contributed to food insecurity among Aboriginal people. The present article takes a closer examination of coping strategies among food insecure households in urban and rural settings in Canada. This includes a comparative analysis of the role of social networks, institutional resources, and diet modifications as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Food reduction strategies to cope with food insecurity and hunger were higher among those living in urban areas than rural and proposed explanations for this included differences in social support networks and barriers to food access such as proximity to food outlets [74]. Zurba et al [75] found that all of the participants in their study were concerned with drug and alcohol addiction for youth in their community, and the relationship between addiction and healthy eating.…”
Section: Dietary Change and Store Foodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Food reduction strategies to cope with food insecurity and hunger were higher among those living in urban areas than rural and proposed explanations for this included differences in social support networks and barriers to food access such as proximity to food outlets [74]. Zurba et al [75] found that all of the participants in their study were concerned with drug and alcohol addiction for youth in their community, and the relationship between addiction and healthy eating.…”
Section: Dietary Change and Store Foodsmentioning
confidence: 99%
“…Tam and colleagues [74] found that a decrease in food intake, including skipping meals, was an informal coping mechanism among food insecure urban Indigenous parents and children. Food reduction strategies to cope with food insecurity and hunger were higher among those living in urban areas than rural and proposed explanations for this included differences in social support networks and barriers to food access such as proximity to food outlets [74].…”
Section: Dietary Change and Store Foodsmentioning
confidence: 99%
See 3 more Smart Citations